The Feedback of the Chinese Learning Diagnosis System for Personalized Learning in Classrooms - You, Xiaofeng; Li, Meijuan; Xiao, Yue; Liu, Hongyun (Frontiers in Psychology, 2019)
Personalized learning is tailoring learning to each student’s strengths and needs. For personalized learning in the classroom, feedback is an essential part and it can provide useful guidance on how to improve learning and/or teaching. The Chinese Learning Diagnosis System (CLDS) adopts cognitive diagnosis theory to offer timely feedback on student learning and teacher instruction. This study mainly describes the feedback of the CLDS into two parts, Part I introduces the feedback report of the CLDS, Party II illustrates its application effectiveness in learning and teaching. Based on the degree of students’ mastery of attribute, teachers might modify their teaching content and schedule, and students have the opportunity to remedy their learning individually. As to the application effectiveness of the CLDS, on the one hand, the experiment results show that students who enrolled in experimental School in 2012 and used the CLDS in their learning have a significant improvement in their self-efficiency and achievement. On the other hand, most teachers indicate that instructional time used for classroom unit tests was reduced by one third to one half. This provides them with large amounts of time to provide more detailed instruction to students individually.